PENGARUH PENGAWASAN, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA CV ONY PERKASA TUNGGAL - Fitri Rezeki (KENDALI: Economics and Social Humanities, 2022)
This study uses a quantitative type with statistical analysis methods carried out with the SPSS version 25 application, in conducting sampling this research uses a simple random sampling technique using the Slovin formula with a total sample of 89 respondents. The purpose of this study was to examine, study, and obtain results how the influence of Supervision, Communication and Work Discipline on Employee Productivity in CV Ony Perkasa Tunggal. The results of this study indicate that: (1) there is a positive and significant effect on the Supervision variable with Employee Productivity CV Ony Perkasa Tunggal. (2) the existence of a positive and significant influence on the Communication variable with Employee Productivity CV Ony Perkasa Tunggal. (3) there is a positive and significant influence on the Work Discipline variable with Employee Productivity at CV Ony Perkasa Tunggal.